2015
DOI: 10.1021/acsami.5b02899
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Hydrogen Evolution Electrodes via Co-Deposition of Platinum and Polyoxometalates

Abstract: A highly active hydrogen evolution reaction (HER) electrode with low Pt loading on glassy carbon (GC) has been prepared by anodic platinum dissolution and co-deposition of polyoxometalates. TEM, EDS, XPS, CV, and ICP-MS analyses gave a Pt loading of 50-100 ng/cm2, corresponding to a Pt coverage of only 0.08-0.16 monolayer. With an overpotential of 65 mV at 20 mA/cm2, the modified GC has a HER activity comparable to that of the commercial Pt working electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 53 publications
3
36
0
Order By: Relevance
“…The first work on HER electrocatalytic activity by POMs was reported in 1985 by Keita and Nadjo . It was also found that co‐deposition of trace amounts of Pt on the working electrode, originating from anodic dissolution of the Pt counter electrode, can be an issue . In 2007, Nadjo's team developed modified surface electrodes for HER based on [H 7 P 8 W 48 O 184 ] 33− , [Co 6 (H 2 O) 30 (Co 9 Cl 2 (OH) 3 (H 2 O) 9 (β‐SiW 8 O 31 ) 3 )] 5− and [(Co 3 ( B ‐β‐SiW 9 O 33 (OH))( B ‐β‐SiW 8 O 29 OH) 2 ) 2 ] 22− .…”
Section: Introductionmentioning
confidence: 99%
“…The first work on HER electrocatalytic activity by POMs was reported in 1985 by Keita and Nadjo . It was also found that co‐deposition of trace amounts of Pt on the working electrode, originating from anodic dissolution of the Pt counter electrode, can be an issue . In 2007, Nadjo's team developed modified surface electrodes for HER based on [H 7 P 8 W 48 O 184 ] 33− , [Co 6 (H 2 O) 30 (Co 9 Cl 2 (OH) 3 (H 2 O) 9 (β‐SiW 8 O 31 ) 3 )] 5− and [(Co 3 ( B ‐β‐SiW 9 O 33 (OH))( B ‐β‐SiW 8 O 29 OH) 2 ) 2 ] 22− .…”
Section: Introductionmentioning
confidence: 99%
“…[105,106] However,the high catalytic performance reported at that time for [SiW 12 O 40 ] 4À was found to be also due to the co-depositiono ft race amountso fP to nt he workinge lectrode, originated from anodic dissolution of the Pt counter electrode. [43,107] In 1992, Rong and Pope also observed the occurrence of hydrogen evolution promoted by aR u-sub-stitutedP OM, a-[PW 11 Ru III (H 2 O)O 39 ] 4À ,i na cidic aqueous solution. [108] Later [104] These POMs were immobilized on carbon black Vulcan XC-72 and deposited on ag lassy carbon electrode (GCE) or confined in poly(vinylpyridine) films on the electrode, which promoted amicroenvironment effect.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 96%
“…The first POM‐based electrocatalyst for HER was reported in 1985 by Keita and Nadjo . However, the high catalytic performance reported at that time for [SiW 12 O 40 ] 4− was found to be also due to the co‐deposition of trace amounts of Pt on the working electrode, originated from anodic dissolution of the Pt counter electrode . In 1992, Rong and Pope also observed the occurrence of hydrogen evolution promoted by a Ru‐substituted POM, α‐[PW 11 Ru III (H 2 O)O 39 ] 4− , in acidic aqueous solution …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations